2017
DOI: 10.3389/fpubh.2017.00057
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Clinical Research in Latin America

Abstract: Enhancing health research capacity in developing countries is a global health priority. Understanding the orthopedic burden of disease in Latin America will require close partnership between more-developed and less-developed countries. To this end, the Osteosynthesis and Trauma Care Foundation assembled a research consortium of Latin-American orthopedic leaders. Prior to the meeting, we surveyed attendees on perceived barriers to conducting research at their institutions. During the event, working groups discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 14 publications
0
13
0
6
Order By: Relevance
“…In addition, the growing prevalence of diabetes mellitus across LatAm and the complexity of the disease suggest opportunities to create or strengthen collaborations towards its prevention and early detection [141][142][143][144]. For example, multinational and multidisciplinary researchpublic health-health care policy-clinical care partnerships which already exist in formal or informal platforms may be well-positioned to evaluate the impact of nutrition, health insurance, housing, and other public policies [79,141,143,[145][146][147][148][149][150][151][152][153][154] on health outcomes and assess their potential translation into preventive strategies at the public health and clinical care levels.…”
Section: Nicaraguamentioning
confidence: 99%
“…In addition, the growing prevalence of diabetes mellitus across LatAm and the complexity of the disease suggest opportunities to create or strengthen collaborations towards its prevention and early detection [141][142][143][144]. For example, multinational and multidisciplinary researchpublic health-health care policy-clinical care partnerships which already exist in formal or informal platforms may be well-positioned to evaluate the impact of nutrition, health insurance, housing, and other public policies [79,141,143,[145][146][147][148][149][150][151][152][153][154] on health outcomes and assess their potential translation into preventive strategies at the public health and clinical care levels.…”
Section: Nicaraguamentioning
confidence: 99%
“…Insufficient institutional (government, academic, etc.) interest or commitment, lack of public awareness on the importance of prevention, insufficient financial and human resources, and political issues are some of the challenges faced across the continent ( 442 444 ). Whereas out of the scope of this review, proposed models of an international collaborative initiative ( 442 ) and of an implementation cycle and a translatability scale for identifying and implementing effective solutions to address the rising burden of chronic diseases in low-middle income countries, specifically CVD ( 444 ), might set the stage for future type 2 DM prevention initiatives in the continent.…”
Section: Preventing Type 2 Dm In Hispanics/latinos—a Holistic Framewomentioning
confidence: 99%
“…On the other hand, its main limitation was the loss of patients during follow-up. Difficulties in clinical research that are usually found in this region 18 contributed to the fact that, from the 123 patients included in the demographic and clinical study, 6 it was only possible to complete the protocol with 92 patients. Due to specific problems in some countries, it was not possible to follow-up all patients for 90 days, as stated in the study protocol.…”
Section: Discussionmentioning
confidence: 99%